EFFECT OF SOAKING TIME ON THE TEMPERATURE-COEFFICIENT OF RESISTIVITY OF SEMICONDUCTING BARIUM-TITANATE PTCR CERAMICS - LU, YY; LAI, CH; TSENG, TY (My University, 1994)
The influence of soaking time at 1200 degrees C on the temperature coefficient of resistivity (TCR) of semiconducting barium titanate ceramics has been investigated. It is found that soaking duration has influence on the room-temperature resistivity, the maximum resistivity, the temperature (T-max) at which the maximum resistivity appears, and TCR of the positive temperature coefficient of resistivity (PTCR) ceramics. The increased room-temperature resistivity with the increase of soaking time is contributed mainly by the increase of grain boundary resistivity examined by the complex-plane impedance method. The obtained surface acceptor density (N-s) by capacitance-voltage measurement is found to increase with the soaking duration. The higher N-s contributes to higher built-in potential and results in lower T-max and higher maximum resistivity. Therefore, the increased surface acceptor density from increasing the soaking time at 1200 degrees C increases the temperature coefficient of resistivity of PTCR ceramics.